In vitro antiplasmodial and cytotoxic properties of some medicinal plants from western Burkina Faso - Souleymane Sanon; Adama Gansane; Lamoussa P. Ouattara; Abdoulaye Traore; Issa N. Ouedraogo; Alfred Tiono; Donatella Taramelli; Nicoletta Basilico; Sodiomon B. Sirima (AOSIS, 2013)
Background: Resistance of malaria parasites to existing drugs complicates treatment, but an antimalarial vaccine that could protect against this disease is not yet available. It is therefore necessary to find new effective and affordable medicines. Medicinal plants could be a potential source of antimalarial agents. Some medicinal plants from Burkina Faso were evaluated for their antiplasmodial and cytotoxic properties in vitro. Methods: Crude dichloromethane, methanol, water-methanol, aqueous and alkaloids extracts were prepared for 12 parts of 10 plants. Chloroquine-resistant malaria strain K1 was used for the in vitro sensibility assay. The Plasmodium lactacte dehydrogenase technique was used to determine the 50% inhibitory concentration of parasites activity (IC50). The cytotoxic effects were determined with HepG2 cells, using the tetrazolium-based colorimetric technique, and the selectivity index (SI) was calculated. Results: Sixty crude extracts were prepared. Seven extracts from Terminalia avicenoides showed IC50 < 5 µg/mL. The IC50 of dichloromethane, methanol, aqueous and alkaloids extracts ranged between 1.6 µg/mL and 4.5 µg/mL. Three crude extracts from Combretum collinum and three from Ficus capraefolia had an IC50 ranging between 0.2 µg/mL and 2.5 µg/mL. Crude extracts from these three plants had no cytotoxic effect, with SI > 1. The other plants have mostly moderate or no antimalarial effects. Some extracts from Cordia myxa, Ficus capraefolia and Opilia celtidifolia showed cytotoxicity, with an SI ranging between 0.4 and 0.9. Conclusion: Our study showed a good antiplasmodial in vitro activity of Terminalia avicenoides, Combretum collinum and Ficus capraefolia. These three plants may contain antiplasmodial molecules that could be isolated by bio-guided phytochemical studies.